Effectiveness of creative arts therapies/expressive arts therapy for psychosocial outcomes in adults with oncological disease: an umbrella review protocol - Svozilová, Magdalena; Kantor, Jirí; Svobodová, Zuzana; Smrčková, Alžběta; Klugar, Miloslav (Frontiers in Psychology, 2025)
This umbrella review will evaluate the effectiveness of creative arts therapies (CAT)—encompassing art, drama, dance/movement, and music therapies—compared to standard non-creative treatments, in enhancing psychosocial outcomes for adults with oncological diseases. Using the JBI methodology for umbrella reviews, we will conduct systematic searches across MEDLINE, Open Dissertations, ProQuest Central, Epistemonikos, and PsycINFO databases, without restrictions on publication year or language. Eligible studies will include systematic reviews of quantitative evidence assessing CAT interventions' effects on psychosocial outcomes, such as depression, anxiety, and quality of life. Screening of studies, qualitative appraisal, data extraction, and data synthesis will be conducted by two independent reviewers. The quality of evidence will be evaluated using the GRADE approach. This protocol is registered with PROSPERO (ID: CRD42023410121).